MAZHAB NEGARA: ALTERNATIF SOLUSI TERHADAP PERBEDAAN PENENTUAN AWAL BULAN QAMARIYAH DI INDONESIA - Marpaung, Wanti (State of Islamic Institute Langsa, 2018)
The article discusses that ?mazhab negara? is a new ideas and solution on muslim?s problem. There are different among moslem Indonesia on starting past Ramadhan, syawal and the others. ?Mazhab Negara? at least will become to clear long time problem among Muslim Indonesia